Kyme Eolica: campagna di scavo 2008 (LANX. Journal of the Scuola di Specializzazione in Beni Archeologici - Università degli Studi di Milano, 2009)
The archaeological excavation, organized by the University of Milan in 2008 in the site of Aeolian Kyme (Aliaga) in Turkey, revealed itself as an important starting point for the studies about the city planning impact of the big theatre (Area V) and about its possible connections with the surrounding quarter. The excavations, still in progress, on the west side of the stage, have drawn attention on a foundation’s assise, with an annexed paving, that would be probably attributed to a stoà.
Keywords: Kyme; area V; theatre; assise; paving; stoà